2008
DOI: 10.1109/tns.2008.919262
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Tolerance of Fully-Depleted P-Channel CCDs Designed for the SNAP Satellite

Abstract: Abstract-Thick, fully depleted p-channel charge-coupled devices (CCDs) have been developed at the Lawrence Berkeley National Laboratory (LBNL). These CCDs have several advantages over conventional thin, n-channel CCDs, including enhanced quantum efficiency and reduced fringing at nearinfrared wavelengths and improved radiation tolerance. Here we report results from the irradiation of CCDs with 12.5 and 55 MeV protons at the LBNL 88-Inch Cyclotron and with 0.1 -1 MeV electrons at the LBNL 60 Co source. These st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 29 publications
3
29
0
2
Order By: Relevance
“…The observed trend in dark current is similar to previously reported behaviour 6 , including the second dip after the first period at room temperature. The other irradiated region follows a similar trend.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…The observed trend in dark current is similar to previously reported behaviour 6 , including the second dip after the first period at room temperature. The other irradiated region follows a similar trend.…”
Section: Resultssupporting
confidence: 90%
“…The increased tolerance to displacement damage of a p-channel CCD was first demonstrated in 1997 2 and since then a number of other studies have demonstrated an improved hardness to radiation induced charge transfer inefficiency (CTI) when compared to n-channel CCDs [3][4][5][6][7] . The improvement has been linked to the number and type of defects formed within the buried channel, 3 and how these defects impact charge transfer, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations